2000
DOI: 10.1097/00000539-200010000-00004
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Superficial Versus Combined (Superficial and Deep) Cervical Plexus Block for Carotid Endarterectomy: A Prospective, Randomized Study

Abstract: Carotid endarterectomy may be performed by using cervical plexus blockade with local anesthetic supplementation by the surgeon during surgery. Most practitioners use either a superficial cervical plexus block or a combined (superficial and deep) block, but it is unclear which offers the best operative conditions or greatest patient satisfaction. We compared the two techniques in patients undergoing carotid endarterectomy. Forty patients undergoing carotid endarterectomy were randomized to receive either a supe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0
6

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(60 citation statements)
references
References 16 publications
2
51
0
6
Order By: Relevance
“…[18][19][20][21][22][23][24] Several studies have shown that the SCPB not only improves pain control after thyroidectomy and carotid endarterectomy, [18][19][20][21][22][23][24] but it also decreases PONV after thyroidectomy. 18 Nevertheless, we did not find any differences in postoperative opioid consumption between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20][21][22][23][24] Several studies have shown that the SCPB not only improves pain control after thyroidectomy and carotid endarterectomy, [18][19][20][21][22][23][24] but it also decreases PONV after thyroidectomy. 18 Nevertheless, we did not find any differences in postoperative opioid consumption between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…As definitions of cervical plexus blocks where hitherto somewhat confusing, the nomenclature has been helpfully systematised, with ICPB defined as the injection of local anaesthetic between the superficial and the deep cervical fascia [15]. In a study by Pandit et al performed in 40 patients, the use of superficial plexus block for carotid endarterectomy using ropivacaine 0.375% provided similar efficacy to that provided by a combined (deep and superficial) cervical plexus block [16]. The volume of supplemental local anaesthesia (approximately 10 ml) needed for the superficial or combined plexus blocks was similar to the one used in this study, although lidocaine 1% was used in Pandit et al's study and lidocaine 2% in ours.…”
Section: Discussionmentioning
confidence: 99%
“…Superficial block is as effective as a deep or combined block if the amount of local anesthetic supplementation by the surgeon is used as a measure of block efficacy, (9) and other measures of block effectiveness (pain scores, postoperative analgesia), which were also not different between the two types of regional anesthesia. (13) …”
Section: Ra: Pros and Consmentioning
confidence: 99%